Enhancing Human Health and Wellbeing through Sustainably and Equitably Unlocking a Healthy Ocean's Potential - Lora E. Fleming; Philip J. Landrigan; Oliver S. Ashford; Ella M. Whitman; Amy Swift; William H. Gerwick; Johanna J. Heymans; Christina C. Hicks; Karyn Morrissey; Mathew P. White; Lota Alcantara-Creencia; Karen A. Alexander; et al. (Ubiquity Press, 2024)
A healthy ocean is essential for human health, and yet the links between the ocean and human health are often overlooked. By providing new medicines, technologies, energy, foods, recreation, and inspiration, the ocean has the potential to enhance human health and wellbeing. However, climate change, pollution, biodiversity loss, and inequity threaten both ocean and human health. Sustainable realisation of the ocean's health benefits will require overcoming these challenges through equitable partnerships, enforcement of laws and treaties, robust monitoring, and use of metrics that assess both the ocean's natural capital and human wellbeing. Achieving this will require an explicit focus on human rights, equity, sustainability, and social justice. In addition to highlighting the potential unique role of the healthcare sector, we offer science-based recommendations to protect both ocean health and human health, and we highlight the unique potential of the healthcare sector tolead this effort.